1990
DOI: 10.1002/j.1460-2075.1990.tb07564.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity dependent regulation of BDNF and NGF mRNAs in the rat hippocampus is mediated by non-NMDA glutamate receptors.

Abstract: The mRNAs of nerve growth factor (NGF) and brain derived neurotrophic factor (BDNF) exhibit a similar, though not identical, regional and cellular distribution in the rodent brain. In situ hybridization experiments have shown that BDNF, like NGF, is predominantly expressed by neurons. The neuronal localization of the mRNAs of these two neurotrophic molecules raised the question as to whether neuronal activity might be involved in the regulation of their synthesis. After we had demonstrated that depolarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
455
2
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 858 publications
(477 citation statements)
references
References 45 publications
(55 reference statements)
18
455
2
2
Order By: Relevance
“…These results imply that the stromal cells which provide a scaffold for trafficking leukocytes or perhaps the sympathetic fibers themselves might be primary NGF sources within the lymph node microenvironment. The later possibility is consistent with previous research indicating activity-dependent release of NGF from neurons (Zafra, Hengerer et al 1990;Hasan, Pedchenko et al 2003), and provides a plausible signaling pathway for transmission of social influences from the central nervous system into the peripheral lymphoid organs.…”
Section: Molecular Mechanismssupporting
confidence: 90%
See 1 more Smart Citation
“…These results imply that the stromal cells which provide a scaffold for trafficking leukocytes or perhaps the sympathetic fibers themselves might be primary NGF sources within the lymph node microenvironment. The later possibility is consistent with previous research indicating activity-dependent release of NGF from neurons (Zafra, Hengerer et al 1990;Hasan, Pedchenko et al 2003), and provides a plausible signaling pathway for transmission of social influences from the central nervous system into the peripheral lymphoid organs.…”
Section: Molecular Mechanismssupporting
confidence: 90%
“…As noted above, analysis of macaque peripheral blood mononuclear cells suggest that lymphocytes are not the primary contributor (< 10% of total lymph node NGF transcription), and catecholamines do not substantially up-regulate NGF expression by leukocytes (Sloan, Capitanio et al 2007b;Sloan, Capitanio et al 2007a;Sloan, Cox et al 2007;Sloan, Nguyen et al 2007). Perhaps sympathetic varicosities are themselves the major NGF releasers in the lymph node (Zafra, Hengerer et al 1990;Hasan, Pedchenko et al 2003)? If so, activity dependent-release of NGF from sympathetic fibers would provide a plausible transmission pathway from the central nervous system, as well as an autocrine stimulus for sympathetic arborization (Hasan, Pedchenko et al 2003).…”
Section: Open Questionsmentioning
confidence: 99%
“…The seizure-induced dendritic targeting of BDNF mRNA is NMDAR dependent. However, Zafra et al (1990) found that kainic acidinduced BDNF expression was not prevented by NMDAR antagonist. Kainic acid can directly activate kainate receptor and thus increase intracellular calcium, which may be sufficient to increase BDNF expression independent of NMDAR activation.…”
Section: Discussionmentioning
confidence: 97%
“…Calcium entry through L-type channels has been shown to play an important role in activity-dependent BDNF expression in hippocampal neurons (Zafra et al, 1990(Zafra et al, , 1991Ghosh et al, 1994;Tabuchi et al, 2000). Therefore, to determine whether calcium entry through L-type channels is capable of regulating release of native BDNF from hippocampal neurons, we exposed hippocampal cultures to 5 M Bay K-8644, a selective agonist of L-type channels (Nowycky et al, 1985;Brosenitsch et al, 1998), in the presence of 15 mM KCl, a protocol that optimizes the efficacy of Bay K-8644 by slightly depolarizing the cells (Brosenitsch et al, 1998).…”
Section: Release Of Native Bdnf Evoked By Patterned Electrical Stimulmentioning
confidence: 99%